Od Pa cho miusza do Benedykta. Officium divinum w reguła ch monas tyczn ych - Wiąckiewicz, Debora Justyna (Studia Theologica Varsaviensia, 2019)
The article presents the issue of the presence and development of officium divinum in the texts of monastic rules from saint Pachomius to saint Benedict, that is from the fourth to the half of the sixth century. Texts of religious legislators presented in a chronological sequence show the consecutive stages of the formation of the liturgical prayer structure by successive generations of monks, and the impact that earlier documents had on later customs and traditions in the framework of the communally celebrated opus Dei.